упростите выражение :1) (√5 - √8) * (√5+√8) 2) (3√175 - √63) : √7 3) √19-(√37) * √19 +(√37) 4) (3√5 - 4)^2 + (12 + √5)^2 5) 6√50 + 11√2 - 4√98
ПОЖАЛУЙСТА!!!!!!

1

Ответы и объяснения

  • Участник Знаний
2013-02-14T18:02:41+00:00

1)(√5 - √8) * (√5+√8) =(√5 - √8) в квадрате= 5-8=-3

2)(3√175 - √63) : √7=325*3-9*7/7=15-3=12

3)√19-(√37) * √19 +(√37) =(√19-√37) в квадрате=19-37=-18

4)(3√5 - 4)^2 + (12 + √5)^2=(9*5-16)+(144+25)=29+169=198

5)6√50 + 11√2 - 4√98=625*2 +112-449*2=6*52+112-4*72=302+112-282=132